SARA’S COOKING PARTY GAME AS A MEDIA TO ENRICH STUDENTS’ ENGLISH VOCABULARY - Daulay, Sholihatul Hamidah; Damanik, Emeliya Sukma Dara; Rahman Hz, Benni Ichsanda; Wandini, Rora Rizky; Reflina; Anggreni, Roziyana (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted to find out of improvement of students’ English vocabulary by using Sara’s Cooking Party game. The population of this study was the grade XI Science2 of Madrasah Aliyah Swasta Amaliyah Sunggal This research was applied by Classroom Action Research. The technique of analyzing data of this study was applied by quantitative data and qualitative data. The quantitative data were taken from the mean of students’ score in taking test. The qualitative data were taken from observation sheet, interview, documentation and diary note. The result indicated that there was an improvement on students’ English vocabulary by using Sara’s Cooking Party game. It was supported by the fact of the mean of the score in every meeting increased. The students’ score in pre-test, the lowest score was 25 point and the highest one was 75 point; the students’ score in post-test I, the lowest score was 60 and the highest one was 85; the students’ score in post-test II, the lowest score was 70 and the highest one was 95. In the pre-test, there were 4.65% (2 of 43 students) who got score ≥ 75. In the post-test I, there were 48.83% (21 of 43 students) who got score ≥ 75. The percentage of the improvement scores from pre-test to post-test I were 44.18%. In the post-test II, there were 93.02% (40 of 43 students) who got score ≥ 75. The percentage of the improvement scores from post-test I to post-test II were 44.18 %. Based on the data, it was concluded the students’ English vocabulary can improve by using Sara’s Cooking Party game.